Getting multi-channel distribution right - Ailawadi, Kusum L.; Farris, Paul W. (Hoboken, New Jersey : John Wiley & Sons, 2020)
"A distribution channel is the chain of distributors, retailers, and other intermediaries through which a supplier's product reaches end consumers, implying a unidirectional movement of goods along a single route, from the point of production to the point of consumption. Even this simple distribution channel is a delicate system, where suppliers and their independent resellers struggle to balance competition for a bigger share of the total profit available in the channel against a cooperative and sustainable partnership. SPEAKING: Both authors speak extensively on the subject throughout the world. Ailawadi has spoken on the topic in the United States, New Zealand, Belgium, Spain, and the Netherlands and is considering events in Italy and Chile. HIGHER ED: Both authors will be using the book int their MBA program classes. EXAMPLES: Examples provided include such companies as: Leather Italia, Brooks Running, Nike, The Honest Company, Pete & Gerry's, Marriott and Choice Hotels, Trip Advisor, Walmart, CVS, and Amazon"--
PART I : THE BEDROCK OF CHANNEL FUNCTIONS, POWER, AND CONFLICT -- PART II : METRICS, TOOLS, AND FRAMEWORKS FOR GETTING THE RIGHT DISTRIBUTION -- PART III : ALIGNING THE MARKETING MIX TO MANAGE DISTRIBUTION.
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
John Wiley and Sons
Keywords: Marketing channels; Circuits de distribution; Marketing channels